Social network analysis of Army Public School Shootings: Need for a unified man-made disaster management in Pakistan. (March 2019) - Azhar, Aisha; Malik, Muhammad Nasir; Muzaffar, Asif
Abstract: This study evaluates the effectiveness of inter-organizational collaboration in response to the Army Public School (APS) Shootings that happened on December 16th, 2014 in the city Peshawar, Pakistan. After reviewing the major changes in terrorism related policies and frameworks before and after September 11, 2002, this article applies a social network analysis to compare the disaster response networks enacted in the formal disaster management plans with the actual response networks formed during the APS attacks. Data were gathered from content analysis of the APS Shootings incident, national and international newspapers, situation reports and after-action reports. The timely response to shootings is attributable to the long term planning efforts of law enforcement agencies. However, for improved results, the response and relief efforts should have been coordinated with the national disaster management framework under the National Disaster Management Authority (NDMA) - the lead authority for disaster management in Pakistan.